2021
DOI: 10.3389/fphys.2021.596596
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Patient-Specific Simulations to Assess Left Atrial Appendage Thrombogenesis Risk

Abstract: Atrial fibrillation (AF) alters left atrial (LA) hemodynamics, which can lead to thrombosis in the left atrial appendage (LAA), systemic embolism and stroke. A personalized risk-stratification of AF patients for stroke would permit improved balancing of preventive anticoagulation therapies against bleeding risk. We investigated how LA anatomy and function impact LA and LAA hemodynamics, and explored whether patient-specific analysis by computational fluid dynamics (CFD) can predict the risk of LAA thrombosis. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(154 citation statements)
references
References 45 publications
6
134
2
Order By: Relevance
“…This suggests that neglecting LA wall motion in CFD simulations might not produce accurate hemodynamics. These results are in accordance with the findings of Garcia-Villalba et al, who demonstrated that simulations with no LA wall motion results in different flow fields as compared to simulations with moving LA walls ( Garcia-Villalba et al, 2021 ). However, our LA wall motion method is based on volume-based interpolation, which might not be representative of the physiological LA wall motion for these patients, which could be a possible reason for modest correlation coefficient.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that neglecting LA wall motion in CFD simulations might not produce accurate hemodynamics. These results are in accordance with the findings of Garcia-Villalba et al, who demonstrated that simulations with no LA wall motion results in different flow fields as compared to simulations with moving LA walls ( Garcia-Villalba et al, 2021 ). However, our LA wall motion method is based on volume-based interpolation, which might not be representative of the physiological LA wall motion for these patients, which could be a possible reason for modest correlation coefficient.…”
Section: Discussionsupporting
confidence: 93%
“…CFD studies have shown that LA hemodynamics is highly dependent on incorporating the LA wall motion in the simulations ( Koizumi et al, 2015 ; Garcia-Villalba et al, 2021 ). To investigate the effect of LA wall motion in our study, we performed simulations for all our models with LA wall assumed as rigid non-moving wall ( Supplementary Material ).…”
Section: Discussionmentioning
confidence: 99%
“…We retrospectively considered the N = 6 left atrial models of García-Villalba et al [35], consisting of 4D (3D, time-resolved) patient-specific segmentations of human left atria obtained from computed tomography (CT) imaging. Three patients had normal LA volume and function, were imaged in sinus rhythm, and did not have a left atrial appendage (LAA) thrombus.…”
Section: Patient Population Image Acquisition Image Reconstruction and Mesh Generationmentioning
confidence: 99%
“…Some of these simulations include models of heart valve motion [22,26,15,17,27,28,29] and some can resolve the intricate domain surface caused by endocardial trabeculation [28,29]. Motivated by the need for patient-specific prediction of LAA blood stasis, the number of CFD simulations of LA flow is growing rapidly [30,31,32,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation